Learning from support workers: Can a dramatherapy group offer a community provision to support changes in care for people with learning disabilities and mental health difficulties?. (10th January 2020) - Bourne, Jane; Selman, Matthew; Hackett, Simon
Accessible summary: Dramatherapy groups are being used to help people with learning disabilities move from hospital back to their homes. The staff who support people to attend the groups talked about their experiences. The staff felt the groups help people stay well, build friendships and get support quickly if needed. The staff felt that the groups were helpful for themselves too as they felt supported and learned new skills. Abstract: Background: The UK Government's Transforming Care Agenda for people with learning disabilities has struggled to meet its goals of reducing inpatient beds and building community‐based support. This article reports on the experiences of support staff who attended dramatherapy groups developed to assist transitions from an inpatient hospital and to prevent re‐admissions through post‐discharge support. The groups provide ongoing support and a place where relationships can be developed between supporter and those supported. Materials and Methods: A focus group with a purposive sample of paid support staff. The data was synthesised using a thematic framework approach. Results: Themes include: (a) new way of supporting and (b) hospital connection. The groups helped improve social interaction, friendship building, communication and self‐confidence. Additional benefits include the pooling of support and a connection with professionals that enables difficulties to be caught early. Conclusions: Support workers valued these dramatherapy groups, recognising how the intervention enabled  people with learning disabilities to develop relationships and provide easy access to mental health professionals. Support staff also found benefits for themselves which included shared support and an increased understanding and insight into the people they support.